2016
DOI: 10.1016/j.ajog.2016.01.194
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in expression of imprinted genes from the H19/IGF2 loci in a multigenerational model of intrauterine growth restriction (IUGR)

Abstract: Background The H19/IGF2 imprinted loci have attracted recent attention due to their role in cellular differentiation and proliferation, heritable gene regulation, and in utero or early postnatal growth and development. Expression from the imprinted H19/IGF2 locus involves a complex interplay of three means of epigenetic regulation: proper establishment of DNA methylation, promoter occupancy of CTCF and expression of microRNA-675 (miR675). We have previously demonstrated in a multigenerational rat model of intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 44 publications
3
22
3
1
Order By: Relevance
“…associated with reduced H19 expression, the imprinted gene integral to fetal growth and development via epigenetic modifications [41]. Strikingly, we found that growth-restricted F2 generation was not prone to develop obesity and associated metabolic disorders, contrary to previous studies [19,40].…”
Section: Female Malecontrasting
confidence: 87%
“…associated with reduced H19 expression, the imprinted gene integral to fetal growth and development via epigenetic modifications [41]. Strikingly, we found that growth-restricted F2 generation was not prone to develop obesity and associated metabolic disorders, contrary to previous studies [19,40].…”
Section: Female Malecontrasting
confidence: 87%
“…142 These epigenetic marks may also be transmitted to future generations. 134,143 This effect has also been demonstrated in animal models, showing that fetal adaptations such as endothelial dysfunction, hypertension, and insulin resistance are passed to the second and third generation of undernourished pregnant rats. 144 The relevance of epigenetics in the adaptation to chronic cardiac failure has been highlighted in human adults, with distinct reported signatures of DNA methylation in cardiac tissue.…”
Section: Expert Reviewsmentioning
confidence: 82%
“…Fifth, the IGF2 locus is a complex genomic region that produces multiple transcripts from alternative promoters, serves different biological functions, and is differentially expressed in different tissues and at different developmental periods. This gene may also shift from monoallelic to biallelic IGF2 promoter methylation during development (Issa, Vertino, Boehm, Newsham, & Baylin, ); can show sex differences in monoallelic tissue‐specific expression via parent of origin genetic effects (Pidsley et al., ); can show loss of imprinting due to diet (Waterland, Lin, Smith, & Jirtle, ); and has important functional genomic relationships (Gonzalez‐Rodriguez et al., ). Therefore, it will be important to establish the extent to which the present results can be replicated and extended with the addition of these molecular and epigenetic mediators and moderators.…”
Section: Discussionmentioning
confidence: 99%